Effects of pH and temperature on growth and glycerol production kinetics of two indigenous wine strains of Saccharomyces cerevisiae from Turkey - Yalcin,Seda Karasu (2008)
The study was performed in a batch system in order to determine the effects of pH and temperature on growth and glycerol production kinetics of two indigenous wine yeast strains Saccharomyces cerevisiae Kalecik 1 and Narince 3. The highest values of dry mass and specific growth rate were obtained at pH 4.00 for both of the strains. Maximum specific glycerol production rates were obtained at pH 5.92 and 6.27 for the strains Kalecik 1 and Narince 3, respectively. Kalecik 1 strain produced maximum 8.8 gL-1 of glycerol at pH 6.46. Maximum glycerol concentration obtained by the strain Narince 3 was 9.1 gL-1 at pH 6.48. Both yeasts reached maximum specific growth rate at 30ºC. Optimum temperature range for glycerol production was determined as 25-30ºC for the strain Kalecik 1. The strain Narince 3 reached maximum specific glycerol production rate at 30ºC. Maximum glycerol concentrations at 30ºC were obtained as 8.5 and 7.6 gL-1 for Kalecik 1 and Narince 3, respectively.